Bisphosphonate-associated osteonecrosis of the jaws - Pankaj Agarwal; Nirmala N Rao (Wolters Kluwer Medknow Publications, 2012)
Bisphosphonates constitute a group of drugs capable of modulating bone turnover and reduce its remodeling when an excessive resorption occurs. This is why they are indicated in a large group of bone diseases like postmenopausal osteoporosis or osteolysis associated with breast cancer or multiple myeloma. Over the last few years and due to their extensive use, many cases of complications associated with their use have been published. Among the most important possible adverse effects are the oral ones, with the appearance of ulcerations and, especially, osteonecrosis of the jaws associated with this therapy. In this paper, we have analyzed the general characteristics of these drugs and their mechanisms of action as well as the described adverse effects, especially oral and maxillofacial, have been made special reference, regarding the prevention of osteonecrosis of the jaws, heightened by cases described in the medical and odontological literature. The preventive protocol backs up the fundamental role of the odontologist in the effective prevention of this process before, during and after the treatment.